2016
DOI: 10.1038/srep37113
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of replica symmetry breaking phenomenology in random laser

Abstract: Random lasers are optical sources where light is amplified by stimulated emission along random paths through an amplifying scattering medium. Connections between their physics and the one of quenched disordered nonlinear systems, notably spin glasses, have been recently suggested. Here we report a first experimental study of correlations of spectral fluctuations intensity in a random laser medium where the scatterers displacement significantly changes among consecutive shots. Remarkably, our results reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…Notably, only one peak appeared in the emission spectra at any value of pump power, indicating incoherent lasing behavior in the cuvette RL system. Similar results have also been reported by Ignesti et al They found that the cuvette RL systems exhibit incoherent random lasing when the scattering mean free path l s is below 1000 µm (in our case, l s ≈ 600 µm) due to the numerous moderately amplified nonresonant lasing modes with strongly spatial coupling . The different lasing behaviors between the POFRLs (coherent lasing) and the cuvette RLs (incoherent lasing) result from the waveguide effect provided by the POFRLs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, only one peak appeared in the emission spectra at any value of pump power, indicating incoherent lasing behavior in the cuvette RL system. Similar results have also been reported by Ignesti et al They found that the cuvette RL systems exhibit incoherent random lasing when the scattering mean free path l s is below 1000 µm (in our case, l s ≈ 600 µm) due to the numerous moderately amplified nonresonant lasing modes with strongly spatial coupling . The different lasing behaviors between the POFRLs (coherent lasing) and the cuvette RLs (incoherent lasing) result from the waveguide effect provided by the POFRLs.…”
Section: Resultssupporting
confidence: 90%
“…With increasing pump powers, the lasing modes disappeared and only one sharp peak (center wavelength: 625 nm, FWHM: 12 nm) was observed in the spectrum. The reason for the vanishing of the lasing modes could be due to the high pump power which excites all the lasing modes in our POFRL . A very large number of the lasing modes with different wavelengths exist in our POFRL system (several thousands) and the spectral distance between each lasing mode is much smaller than the resolution of our spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…6, the RL threshold also marks the sharp phase transition from the qmax ≅ 0 replica-symmetric paramagnetic prelasing regime to the qmax ≅ 1 spin-glass RL phase with RSB. This coinciding behavior, firstly demonstrated in a 3D RL [82], is thus also shared by the Er-RFL system, although a recent report [97] has pointed that this might not be a universal property of RL systems. Therefore, though a complete theoretical understanding of such finding is still lacking, it is possible to trace back the common physical origin of the Lévy and glassy behaviors to the Langevin equations for the amplitudes of the normal modes, which, as discussed, are the basis to explain both the statistical regimes of intensity fluctuations and the photonic RSB spin-glass behavior of RL systems.…”
Section: Lévy Statistics and Glassy Behavior In Er-rflmentioning
confidence: 92%
“…They also theoretically predicted the RSB phase transition can be found in a RL system with quenched disorder . Thereafter, many studies reported that the RSB phenomenon can be observed in different RL system with different configuration such as Er‐doped fiber laser with random grating, Rhodamine B laser dye solution with ZnO nanoparticles, and Rhodamine 6G laser dye solution with specially designed TiO 2 nanoparticles . Thus, using spin‐glass theory to analysis, the statistical behavior of the RL system provides a new approach to understand the physical mechanism inside the RL.…”
Section: Introductionmentioning
confidence: 99%